1981
DOI: 10.1113/jphysiol.1981.sp013657
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery from depolarizing drugs in rat diaphragm.

Abstract: SUMMARY1. The end-plate region in surface fibres of rat diaphragm was located by the use of polarizing filters.2. Carbachol (100,M) produced depolarization at the end-plate to -55 mV, as shown by continuous recording, with some indication of spontaneous recovery in the presence of the drug. The miniature end-plate potentials disappeared and remained absent.3. By repeated sampling it was found that the resting potential at the end-plate had largely recovered after 45 min in the presence of carbachol. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The depolarization produced by carbachol in rat diaphragm is followed by spontaneous recovery in the presence of the drug, and this repolarization has been interpreted in terms of a metabolically driven sodium-potassium transfer pump (Creese & Mitchell, 1981). In the present study the prolonged effects ofdecamethonium have been examined in denervated guinea-pig diaphragm, in which net movements of potassium and subsequent recovery can also be demonstrated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The depolarization produced by carbachol in rat diaphragm is followed by spontaneous recovery in the presence of the drug, and this repolarization has been interpreted in terms of a metabolically driven sodium-potassium transfer pump (Creese & Mitchell, 1981). In the present study the prolonged effects ofdecamethonium have been examined in denervated guinea-pig diaphragm, in which net movements of potassium and subsequent recovery can also be demonstrated.…”
Section: Introductionmentioning
confidence: 95%
“…Electrical recording. In rat diaphragm the end-plates were localized and the effects of decamethonium were studied by continuous recording and by repeated puncture (Creese & Mitchell, 1981). For denervated guinea-pig diaphragm the strip of muscle was set up horizontally in flowing saline and similar recording methods were used.…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistency may be explained if the effect of carbachol were to have been limited by desensitization of the endplate cholinoceptors. In our experiments with ECO, m.e.p.ps were present, but the m.e.p.ps of rat diaphragm 'promptly disappeared' in the presence of 10-M carbachol (Creese & Mitchell, 1981), and the endplate current due to carbachol applied to guinea-pig diaphragm declined rapidly over the first 5min (Creese et al, 1987). Furthermore, Bray et al (1982) found that m.e.p.ps were unaffected by 10-7 M carbachol but reduced by 106 M. Thus it is considered that the accumulation of Ca after carbachol was limited by desensitization and the accumulation due to non-quantal release of ACh after ECO was not limited to the same extent.…”
Section: Methodsmentioning
confidence: 91%
“…Spontaneous repolarization in rat muscle has been attributed to desensitization plus Na-K pump action stimulated probably by intracellular Na+ gain (Creese & Mitchell, 1981), and similar mechanisms are likely to occur in guinea-pig diaphragm. The carbacholinduced end-plate current inferred from Fig.…”
Section: Spontaneous Repolarization and Pump Actionmentioning
confidence: 99%
“…In rat muscle spontaneous recovery of membrane potential in the presence of depolarizing drugs has been demonstrated by Creese & Mitchell (1981), but their analysis was limited by the necessity to make repeated impalements with microelectrodes. Spontaneous recovery of potential is also found in muscle fibres of guinea-pig diaphragm, with the advantage that in this preparation the fibres are larger and recovery occurs with micro-electrodes in position.…”
Section: Introductionmentioning
confidence: 99%